University social and business practices in virtual environments: A study case in DEAD UAM in Colombia (Innovaciones Educativas, 2022)
This article is an essay on the Distance Learning Department of Universidad Autónoma de Manizales (DEAD-UAM Colombia) in charge of systematizing the experience of three business and social practices in the virtual programs of the administration and business areas in the period corresponding to 2014-2020. The study has a mixed-methods research design with a descriptive scope characterizing the processes involved in each teaching practice. It evaluates the digital didactic sequences used and presents the main outcomes regarding coverage, beneficiaries, and projects being carried out. Considering that the literature regarding virtual business and social practices in universities is scarce in Spanish, this experience shows that using MEC Complexus (Convergent Environment Model) allows TICs to be used intentionally to build contextualized digital didactics to help network building between universities, business, and territories.  In this fashion, TIC-mediated higher-education practices under a supporting didactic model can shorten geographical distances boosting access so the students can get to the end of the term improving their social and professional skills in real organizational contexts.
Keywords: pedagogical practice; educational evaluation; information technologies; distance learning; practical tasks